How Does Trade Policy Uncertainty Affects Innovative Behavior in Export-Oriented Enterprise: Evidence From Listed Export Companies of Chinese - Pei Xu; Zehu Jin; Xianghua Wu (Discrete Dynamics in Nature and Society)
This paper discusses the impact of trade policy uncertainty (TPU) on innovative behavior in export-oriented enterprises using data of nonfinancial Chinese A-share listed companies from 2007 to 2021. TPU index is constructed using a tariff measurement method and a text mining method after China’s accession to the WTO. The findings reveal that (1) the decrease in TPU promotes export-oriented enterprises’ innovative input and output, and the positive effect is even more pronounced in eastern export-oriented enterprises, general trade enterprises, and enterprises whose export destination is the high-income countries. (2) For analyzing the transmission mechanism, it is found that the export scale, the financing restriction, and the digital transformation play positive intermediary roles, respectively, in the innovative behavior. The conclusions provide not only theoretical support to cope with TPU but also decision-making reference on improving the innovative performance of export-oriented enterprises.